Strategy for reducing inventory turnover in a manufacturing enterprise - Kashtalian, Tetiana (Management and Entrepreneurship: Trends of Development, 2025)
Manufacturing companies wanted to shorten the holding time and increase the turnover without service. This article synthesizes evidence of fifteen colleagues of studies to identify strategies that reduce DIO (DIO) of the day and improve stock turnover (IT). Directed by structured discovery and transparent inclusion criteria we review strict, empirical, field analysis, slim storage and lack of waste, modified smoothed MRPs and orders, adjournment, suspension, vertical integration, vertical integration, vertical integration and surprise. The data was extracted on the design, reference, matrix and effects; The quality of the study and the risk of distortion was evaluated. The synthesis of legends, a supplement where the measures were comparable, indicate continuous DIO sections from lean implementation and removal of warehouse waste, reduce variability in storing policies with other benefits. Integration and information strengthen the effects of visibility; On the other hand, configuration warehouses "very oak" risk, especially under unstable demand. The slight results of the industry and the fixed scale and the inequality in the range of metrics are estimated. The consequences are practical: segment of SKU, a few slender flows with disciplined rules of safety tracks, stabilization of commands by adapting MRP and expanding cooperation upstream. The boundaries include the measurement of the non -ecosity and potential distortion of the publication. In the end, we closed the implementation plan and proposed a proposal for the cause to separate the power of the mechanism in future research. JEL Classification: M11 L23 D24